Gen Z’s Preference for English Digital Learning Media - Qatrunnada, Agatha Fitri; agustina, Eliasanti; Setiawan, Rahmat (Universitas Nurul Jadid, 2025)
This study explores the preferences of Generation Z for English learning media and the factors influencing these preferences. Generation Z, born between 1997 and 2012, demonstrates a strong inclination toward modern digital platforms such as social media, video streaming services, and learning apps like Duolingo, which offer flexibility, interactivity, and visually appealing content. The study employs a mixed-method approach, combining quantitative surveys of 77 respondents aged 15–25 years and qualitative interviews with four participants. Key findings reveal that ease of access, visual appeal, and relevance to personal interests significantly influence Gen Z’s media choices. Challenges include distractions, short attention spans, and a lack of motivation in self-directed learning. The findings highlight the importance of designing media that aligns with Gen Z’s learning styles, incorporating interactive and gamified elements to enhance engagement and learning outcomes. This research provides valuable insights for educators and developers to optimize digital media for effective English learning